Photodiodes based on graphene oxide-silicon junctions - Phan, D. -T.; Gupta, R. K.; Chung, G. -S.; Al-Ghamdi, A. A.; Al-Hartomy, Omar A.; El-Tantawy, F.; Yakuphanoğlu, Fahrettin (Pergamon-Elsevier Science Ltd, 2012)
Schottky barrier diode based on graphene oxide (GO) with the structure of Al/GO/n-Si/Al was fabricated. The current voltage characteristics of the diode were investigated under dark and various light intensity. It was observed that generated photocurrent of the diode depends on light intensity. Various junction parameters were presented using I-V characteristics. The transient photocurrent measurement indicated that the Al/GO/n-Si/Al diode was very sensitive to illumination. The photocurrent of the diode increases with increase in illumination intensity. The capacitance voltage frequency (C-V-f) measurements indicated that the capacitance of the diode depends on voltage and frequency. The capacitance decreases with increasing frequency due to a continuous distribution of the interface states. These results suggest that the Al/GO/n-Si/Al diode can be utilized as a photosensor. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Graphene oxide; Schottky diode; Photoconductor; Ideality factor; Barrier height